Pengembangan Handout Stunting Sebagai Upaya Meningkatkan Pemahaman Konsep Mahasiswa Pendidikan Jasmani UNIKI - Annisha, Dini; Novayanti, Sri (Jurnal Paedagogy, 2022)
The study aims to develop handout teaching materials on stunting material implemented in Physiology courses to measure the level of understanding of student concepts. This study used the ADDIE model’s R&D (research and development) methods. The research was conducted on UNIKI Physical Education study program students in semester two, totaling 100 people. The research instrument was a questionnaire to test the validity, practicality, and legibility of stunting handouts and conceptual understanding tests. The data analysis technique was used to test the validity and practicality of the handout using percentage score analysis through a validation questionnaire sheet. While the effectiveness test used a 25-item question instrument, the data was analyzed using SPSS 22.00 software statistical analysis testing. The results of this study showed that the stunting handout was very valid and feasible to be used as teaching material to measure the level of conceptual understanding with the acquisition of a score. Moreover, the stunting handout was very valid and feasible to be used as teaching material to measure the level of conceptual understanding with the acquisition of scores, namely: 90% media experts; 94.2% teaching material design experts; 87% material experts; 90% field practitioners; 90% readability by students. Then the effectiveness test results showed that the Sig (2-Tailed) value was 0.000 <0.05. It showed that there was a difference in the first and post-test scores. Thus, proving stunting material handouts in the Physiology course improves students’ conceptual understanding.